Pregnancy in Wilson's disease: management and outcome - Pfeiffenberger, Jan; Gotthardt, Daniel; Haag, Nicola; Gauss, Annika; Stremmel, Wolfgang; Weiss, Karl Heinz (Hepatology, 2018)
Wilson's disease (WD) is a rare inherited disorder of copper metabolism causing toxic hepatic and neural copper accumulation. Clinical symptoms vary widely, from asymptomatic disease to acute liver failure or chronic liver disease with or without neuropsychiatric symptoms. Continuation of specific medical treatment for WD is recommended during pregnancy, but reports of pregnancy outcomes in WD patients are sparse. In a retrospective, multicenter study, 282 pregnancies in 136 WD patients were reviewed. Age at disease onset, age at conception, and WD-specific treatments were recorded. Maternal complications during pregnancy, rate of spontaneous abortions, and birth defects were analyzed with respect to medical treatment during pregnancy. Worsening of liver function tests was evident during 16 of 282 (6%) pregnancies and occurred in undiagnosed patients as well as in those under medical treatment. Liver test abnormalities resolved in all cases after delivery. Aggravation of neurological symptoms during pregnancy was rare (1%), but tended to persist after delivery. The overall spontaneous abortion rate in the study cohort was 73 of 282 (26%). Patients with an established diagnosis of WD receiving medical treatment experienced significantly fewer spontaneous abortions than patients with undiagnosed WD (odds ratio, 2.853 [95% confidence interval, 1.634-4.982]). Birth defects occurred in 7 of 209 (3%) live births. Conclusion: Pregnancy in WD patients on anticopper therapy is safe. The spontaneous abortion rate in treated patients was lower than that in therapy-naïve patients. Although the teratogenic potential of copper chelators is a concern, the rate of birth defects in our cohort was low. Treatment for WD should be maintained during pregnancy, and patients should be monitored closely for hepatic and neurological symptoms. (Hepatology 2018;67:1261-1269).